Microbial, Biochemical, Anatomical and Histochemical Analysis of Black Pepper and Sorghum Inoculated with Mycorrhiza - C.K. Suresh, K.V. Rajesh, C. Sandeep*, (Journal of Phytology, 2011)
Microbial, biochemical and histochemical analysis of Black pepper (Piper nigrum L.) and sorghum (Sorghum bicolor L. Moench) inoculated with mycorrhiza from the organic soil, inorganic soil, natural soil, control and Glomus fasciculatum was studied. Microbial population and activity of different enzymes in soils of pepper and sorghum inoculated with mycorrhiza and control plants were studied. The anatomical studies showed that there were striking differences in plant leaf structures. Sizes of upper epidermis, lower epidermis, xylem cells and spongy layer increased due to inoculation with mycorrhiza from the organic soil, inorganic soil, natural soil, control and Glomus fasciculatum. Histochemical analysis of these crop plants were carried out to study the difference in the accumulation of the polysaccharides, proteins and nucleic acids in leaf tissues of control and mycorrhiza inoculated plants. There was increased accumulation of protein, polysaccharide and the nucleic acids in the leaf samples indicating the direct correlation between the Arbuscular MycorrhizalÃ‚Â  (AM) fungi and the crop response to inoculation of the AM fungi. The growth parameters studied were stem girth, rooting percentage and sprouting percentage. Mycorrhizal association with pepper and sorghum was also studied.